Tessuti di seta tra Firenze e il Levante (ca. 1350-1550) Le fonti - GUIDI BRUSCOLI, FRANCESCO (Biblioteca di storia, 2023)
This study, through the use of hundreds of archival documents over a period of about two centuries, highlights the total reversal in the silk trade that occurred from the beginning of the 15th century: silk cloth no longer crossed the Mediterranean from East to West, as in previous centuries, but from West to East. Jewish, Turkish and Syrians merchants, and above all the Sublime Porte showed continued appreciation for Florentine silks. Through the analysis of the sources, every phase of such export is described in detail: the purchase of the cloths in Florence, their shipment, transport and finally the sale through Florentine correspondents in Constantinople. This flow of silks continued until the first decades of the 16th century, only to decline rapidly around the middle of the century.